Pengaruh Kualitas Produk dan Nilai Pelanggan terhadap Loyalitas Pelanggan Simcard GSM Simpati PT Telkomsel (Studi Kasus pada Mahasiswa S1 Fakultas Ilmu Sosial dan Ilmu Politik Universitas Diponegoro Semarang) - Putri, Sukmawati Resa; Prihatini, Apriatni Endang; Nurseto, Sendhang (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
This research is motivated by the development of mobile operators in Indonesia in its journey was not immediately successful as it is now. There is a process and the time that it takes to be a reliable provider. The mobile phone is no longer a luxury item that use only wear certain circles. From adults to children, cellular phone is already a common goods and are also easy to use to communicate. However, based on the pre-study, researchers get the fact that there is a decline in customers to use GSM simcard simpati since the presence of competitors GSM provider. The purpose of this study was to determine the effect of product quality and customer value on customer loyalty GSM simcard simpati S1 case studies on the Faculty of Social and Political Sciences. This type of research is explanatory research. document collection methods used were questionnaires, interviews, and observations. The sample in this study amounted to 100 respondents using a sampling technique using multi-stage sampling technique and purposive sampling . Linear regression analysis and significance test is used to prove the hypothesis using SPSS.The results of this study show that in partial product quality has a positive effect on customer loyalty simpati. While the value of the variable customer has a positive effect on customer loyalty and simapati GSM simcard is the variable with the greatest influence. Simultaneously, the variable quality of the customer and the customer has an influence on the value of customer loyaitas by 32.6%. Based on the results of the study, the researchers suggested the company to improve product quality attention, especially if the signal strength is in a rural and mountainous areas, ease of facilities / features, reproduce cheap promo surf and phone at an affordable price by the students so as to increase customer loyalty to use GSM simcard simpati.